Human Development and Migration - Grubba, Leilane Serratine (2021)
The article addresses the need for a new definition of Refugee status, facing this as one of the reflexes of globalization and transnationalism. We introduce the theme with consideration of transnationalism and globalization, as well as an examination of the implications that it inevitably has caused in the world reality. Therefore, we analyze a new approach related to Human Rights, problematizing the current migratory waves. Also, we question the relationship between environmental and economic migrations, based on the specific cause of each modality. The hypothesis we offer is the need to rethink both modalities of migration in order to conceptualize them as a refuge, considering that the cause of this kind of migration seems to be the results of globalization and transnationalism. Thereby, the conceptual and juridical existence of economic and environmental refugees is postulated; contemplating the urgency of a new category for displaced people and the need for a new definition that understands the recent approach to state power. In this perspective, we problematize the current migratory waves from a global and transnational vision